Pemahaman Makna dalam Interaksi Lisan dan Tulisan dalam Studi Kasus Conversation, Speech, and Written Text - Anisa Rahmawati; Diah Cahyani; Halim Fratama; Rizqina Az Zahra; Davin Ade Putra Pratama; Nur Adila Nasution; Khusnul Khotimah (INDO PUBLISHING, 2025)
The meaning of written text, conversation, speech, and written text generally refers to different but related types of communication in linguistics. Written text is a form of communication that is systematically and completely arranged in writing, which can be understood independently without the presence of the speaker. Conversation is oral communication that takes place interactively, spontaneously, and bidirectionally, relying on context and direct feedback between participants. Meanwhile, speech is a form of oral communication that is structured and formal, such as a speech delivered to an audience with a specific purpose. Linguistically, text can encompass both written and spoken language as a unified whole of meaning, each having different functions and structures according to the context of use. Written text requires the proper use of grammar and punctuation to convey the message clearly, while oral communication is more flexible and influenced by intonation, pauses, and non-verbal expressions..